ANALYSIS ON FINANCIAL DISTRESS USING ALTMAN Z-SCORE, SPRINGATE, AND ZMIJEWSKI METHODS IN TELECOMUNICATION COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Zaidatun Ekastuti; Nafisa Haura Nur Elandta; Sudarsono Sudarsono; Ira Phajar Lestari; Hendri Rahmayani Asri (Universitas Gunadarma, 2024)
This study aims to predict and analyze the potential for financial distress in telecommunications companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2022 period using the Altman Z-Score, Springate, and Zmijewski models. The type of data used is secondary data in the form of financial statements of telecommunications companies listed on the IDX for the 2019-2022 period. The analysis was carried out using the financial distress prediction method of the Altman Z-Score, Springate, and Zmijewski models. The results showed that there were three companies predicted to have potential financial distress using the Altman Z-Score and Springate models during the observed year. While the calculation results with the Zmijewski Model in 2019 and 2020 there is one company that is predicted to potentially experience financial distress.